HEALTH INDICATORS AND HDI: PANEL EVIDENCE FROM WEST JAVA - Fita Purwaningsih; Muhammad Nurhikmat; Resi Pratiwi; Aso Sukarso (Universitas Negeri Semarang, 2026)
Measuring regional development through the Human Development Index (HDI) carries an inherent limitation: its composite structure tends to smooth over disparities that persist at the sub-provincial level, especially in health. Drawing on a balanced panel of 27 districts and cities in West Java (2019–2023, N = 135), this paper examines whether four operational health inputs—sanitation coverage, national health insurance enrolment (JKN/BPJS), self-reported morbidity, and child undernutrition—translate into measurable HDI differences across time within each district. Secondary data from BPS, BPJS Kesehatan, and the Ministry of Health were analysed with a fixed-effect estimator, chosen following Chow and Hausman specification tests; robust standard errors clustered at the district level correct for heteroskedasticity and serial correlation. JKN/BPJS enrolment exerts the strongest influence (β = 0.273, p < 0.01), while child undernutrition consistently depresses HDI (β = −0.011, p < 0.01). Sanitation reaches significance but its within-district coefficient is unexpectedly negative; morbidity is negative yet statistically insignificant. Together the regressors account for roughly 45 per cent of within-district HDI movement. Accelerating JKN utilisation quality and multi-sectoral undernutrition programmes emerge as the highest-leverage entry points for local governments seeking to advance human development in West Java.